2016
DOI: 10.1002/gea.21550
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Hispanic and Colonial Flood Plain Destabilization in the Texcoco Region and Lower Teotihuacan Valley, Mexico

Abstract: Stratigraphic sequences in the flood plains of the eastern Basin of Mexico reveal episodes of intense flooding in the past 3000 years, represented by the deposition of alluvial units C, D, and E, and their respective soil horizons. Unit C correlates with the initial growth of population and clearance of vegetation in the piedmont during the Formative period, followed by a stable period ca. 200 B.C. to A.D. 800 represented by a dark A‐horizon (soil S3). Unit D is associated with land use changes in the Late Cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…As such, precise environmental conditions during the settlement of the Teotihuacan Valley in the Formative Period (1500 B.C.-A.D. 100) remain unclear. Firm evidence for the Teotihuacan/Classic Period (A.D. 100-650) climate is also scarce, but grass phytoliths from radiometrically dated contexts in the surrounding valleys suggest that the climate was similar but possibly drier than it is today (Cordova, 1997;Solleiro-Rebolledo et al, 2006). Meanwhile, speleothem and dendrochronological evidence suggest that the modern timing of monsoonal rains has been present since at least one century after the city's collapse (Kennett & Marwan, 2015;Lachniet, Bernal, Asmerom, Polyak, & Piperno, 2012;Stahle et al, 2011).…”
Section: Landscape and Climate In The Teotihuacan Valleymentioning
confidence: 99%
See 3 more Smart Citations
“…As such, precise environmental conditions during the settlement of the Teotihuacan Valley in the Formative Period (1500 B.C.-A.D. 100) remain unclear. Firm evidence for the Teotihuacan/Classic Period (A.D. 100-650) climate is also scarce, but grass phytoliths from radiometrically dated contexts in the surrounding valleys suggest that the climate was similar but possibly drier than it is today (Cordova, 1997;Solleiro-Rebolledo et al, 2006). Meanwhile, speleothem and dendrochronological evidence suggest that the modern timing of monsoonal rains has been present since at least one century after the city's collapse (Kennett & Marwan, 2015;Lachniet, Bernal, Asmerom, Polyak, & Piperno, 2012;Stahle et al, 2011).…”
Section: Landscape and Climate In The Teotihuacan Valleymentioning
confidence: 99%
“…Furthermore, every known irrigation canal dating to the Teotihuacan period is floodwater based-that is, rainfed-and exists up-valley from the springs (Aguilera Muñoz, 1997; Armillas, Palerm, & Wolf, 1956;Cabrera, 2005;Cabrera & Gómez, 2008;Charlton, 1977Charlton, , 1978Charlton, , 1979aCharlton, , 1979bGómez & Gazzola, 2004;Mejía Ramón, 2016Millon, 1957;Nichols, 1987aNichols, , 1988Nichols et al, 1991;Sanders, Nichols, Storey, & Widmer, 1982;Sanders, West, Fletcher, & Marino, 1972). The missing data may be due to the exceptionally deep soils downstream from the springs (Cordova, 2017;Skopyk & Martínez-Yrizar, 2012), although excavations near the springs have failed to find such permanently fed hydraulic features for maize agriculture (Gómez & Gazzola, 2004;González Quintero & Sánchez Sánchez, 1991).…”
Section: Landscape and Climate In The Teotihuacan Valleymentioning
confidence: 99%
See 2 more Smart Citations
“…Estimates of potential agricultural productivity implied that the region could sustain dense populations (Charlton 1970; Lorenzo 1968), although later population estimates for the urban zone alone suggested that a significant proportion of basic subsistence resources had to have been acquired from a much broader area (McClung de Tapia 2012). Recent research indicates that prior estimates of agricultural potential were based on modern soils, which developed on redeposited sediments (Cordova 2016; González-Arqueros et al 2013; Sánchez-Pérez et al 2013). A black soil with vertic properties overlying the tepetate, the volcanic bedrock in this region, had been observed by archaeologists in different sectors of the region (Charlton 1972; Nichols 1987; Widmer 1987); its significance, however, was unrecognized at the time.…”
Section: Introductionmentioning
confidence: 99%